Response of Nitrogen and Phosphorus Fertilizer and Plant Spacing on Growth and Yield Contributing Character of Sunflower (Bangladesh Journal of Scientific and Industrial Research, 2007)
The plant spacing of 20, 25 and 30 cm were used for the study. The doses of nitrogen and phosphorus were 80, 100, 120 and 45, 60, 75 kg/hectare respectively. The experiment was carried out in a randomized block design with three replications. 20 cm plant spacing produced the highest plot yield. Maximum number of seeds per head and yield were produced by the application of 120 kg N + 75 kg P2O5 per hectare. In case of plant spacing x fertilizer interaction effect, 20 cm plant spacing with 120 kg N + 75 kg P2O5 per hectare treatment produced the highest head diameter and seed yield. Bangladesh J. Sci. Ind. Res. 41(1-2), 33-40, 2006